Penguatan Konsep Dasar Matematika Melalui Kegiatan Math Club Berbasis Permainan pada Siswa SMPN 4 Majene - Helmi Helmi; Gita Oktavia; Sartika Arifin; Fauziah Hakim; Nursakinah Annisa Lutfin; Nurlina Nurlina (Rengganis Jurnal Pengabdian Masyarakat, 2026)
Mathematics is often considered a difficult subject by students. Even now, many students still have not mastered basic mathematical concepts even though they are in grade 9 of junior high school. Therefore, this community service activity aims to strengthen students' basic mathematical concepts through Math Club activities using domino games at SMPN 4 Majene. This activity involved 40 students from grades 7, 8, and 9 who participated in structured meetings. This Math Club activity was held from September to November 2025. In the Math Club activity, the team used the domino game as media to make the activity more enjoyable and meaningful for students. The domino game media was in the form of question-answer cards that were adjusted to the curriculum and the difficulty level of each grade level. The implementation method consisted of three stages: preparation, implementation, and evaluation. Data were collected through pre-tests and post-tests to measure improvements in basic mathematical concepts, as well as questionnaires to measure student interest and satisfaction. The results of the activities showed an improvement in basic mathematical concepts and students participated actively and enthusiastically in each series of Math Club activities.